pre calc

(cos^2)3x+(sin^2)3x=cos(f(x))
simplify expression and find f(x)

  1. 👍 0
  2. 👎 0
  3. 👁 43
asked by dylan
  1. cos^2+sin^2=1
    so f(x) = 0

    1. 👍 0
    2. 👎 0
    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. pre-cal

    Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos 6x can be expressed as a series of terms that involve sin x or cos x only, but the end result is not a simplification. sin 2x = 2 sinx cosx cos 6x = 32 cos^6 x

    asked by ethan on May 17, 2007
  2. algebra

    Can someone please help me do this problem? That would be great! Simplify the expression: sin theta + cos theta * cot theta I'll use A for theta. Cot A = sin A / cos A Therefore: sin A + (cos A * sin A / cos A) = sin A + sin A = 2

    asked by Valerie on February 18, 2007
  3. TRIG!

    Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x +

    asked by hayden on February 23, 2009
  4. Math(Please check)

    Use the fundamental identities to simplify the expression. tan^2 Q / sec^2 Q sin^2/cos^2 / 1/cos^2 = sin^2 / cos^2 times cos^2 / 1 = The cos^2 cancels out so sin^2 is left. Is this correct?

    asked by Hannah on March 5, 2010
  5. Precal

    I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A + cos A) ) = 1 - sin A cos A note that all the trig terms are closed right after there A's example sin A cos A = sin (A) cos (A) I wrote it out like this 0 = -

    asked by Joe on January 14, 2010
  6. tigonometry

    expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b)

    asked by Pablo on November 26, 2006
  7. trig

    Reduce the following to the sine or cosine of one angle: (i) sin145*cos75 - cos145*sin75 (ii) cos35*cos15 - sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b) - sin(a)sin)(b) (1)The

    asked by Paul C on November 26, 2006
  8. Pre-Cal

    Write the trigonometric expression in terms of sine and cosine, and then simplify. 1). (csc θ − sin θ)/(cos θ) ____________. 2). Simplify the trigonometric expression. (cos u + 1)/(sin u) + (sin u)/(1 + cos u) ______________.

    asked by Amber on July 6, 2016
  9. Math

    Write the expression in terms of costheta and then simplify. cos^4theta - sin^4theta + sin^2theta Ans: cos^4 θ - 1 - cos^4 θ + 1 - cos^2 θ = -cos^2 θ

    asked by Anonymous on June 2, 2015
  10. Mathematics - Trigonometric Identities

    Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) =

    asked by Anonymous on November 8, 2007
  11. precalc

    Find the exact value of each expression, if it exists: the -1 are representing the inverse functions! (a) sin -1 (-√2/2) (b) cos−1 (−1) (c) sin( 􏰀sin−1 (π)􏰁) (d) cos−1􏰀(cos􏰀(−4π􏰁􏰁/ 3)) (e) tan−1

    asked by help! on April 17, 2016

More Similar Questions